Self-reported physical activity in perceived neighborhood in Czech adults - national study - Josef Mitáš; Karel Frömel; Svatopluk Horák; Jiří Nykodým; Oldřich Racek; Emil Řepka; Zdeněk Šebrle; Ladislav Bláha; Aleš Suchomel; Dana Feltlová; Igor Fojtík; Petr Valach; et al. (Palacky University, 2013)
BACKGROUND: International studies associate physical activity (PA) to other factors such as the environment, culture, and policy. External influences on lifestyle and PA, such as the effect of the physical and built environment, are discussed. Neighborhood environments seem to be one of the important aspects in prevention of unhealthy lifestyle and physical inactivity research. OBJECTIVE: The main objective is to analyze the relationship between PA and neighborhood environment of the adult population of the Czech Republic. The study tries to define the basic correlates of PA in relation to environmental and other socio-demographic factors. METHODS: Nationwide data collection of adult PA was done regionally in the Czech Republic between the years 2005-2009 using the IPAQ (long) and ANEWS questionnaires. RESULTS: The results show that males realize significantly more vigorous PA than females while females realize more moderate PA and walking than males. PA of residents of smaller communities is higher than those living in large cities. The level of weekly PA does not significantly affect the neighborhood walkability [H(3, 8708) = 19.60; p < .001; η2 = .002]. CONCLUSIONS: The results clearly indicate the need to connect multiple sectors that affect the lifestyle of the general population. Possible solution is an interdisciplinary approach to the evaluation of the fundamental environmental factors influencing the level of PA (walkability; SES; participation in organized and voluntary PA; neighborhood safety; type of transportation; size of the community).